Impact of Biological Fertilizer Under Integrated Nutrient Management on Growth and Physiology of Rice (Oryza sativa L.): Physiology of Rice Seedling (Biological Sciences - PJSIR, 2025)
To enhance the efficiency and productivity of rice seedlings, Post Harvest Lab., Department of Agriculture and Agribusiness Management, University of Karachi conducted a study to analyse the interactive effects of synthetic and biofertilizers on the physiology of rice seedlings. Individual and interactive effects of reclaimer (R), biozote (B), Trichoderma (T), urea and DAP on the productivity of rice seedlings were studied through a 5-inch pot on the open-pollinated, non-aromatic rice variety Pk-386. Different treatments of the individual biofertilizer and its mixture with synthetic fertilizers were used to assess the effects on germination, plant length, vigour, fresh weight, dry weight as well as moisture percentage. 3170.2 was the highest vigour recorded in the treatment of Trichoderma T with synthetic and biofertilizers. The highest moisture of 76.5% was calculated in the treatment of Trichoderma T with biofertilizers. Under the interactive combination of synthetic and biofertilizers, many treatments of biofertilizer mixture improved the major growth parameters of rice seedlings.